Michigan - Dubois, Muriel L. (Milwaukee, WI Gareth Stevens Publishing, 2006)
Each volume provides a colorful, comprehensive portrait of a state's history, people, land, economy, and government.
Elementary
Keywords: Michigan; Portraits of the States